Effects of prior activity on the conduction in single motor units in man. Issue 4 (April 1983) - Borg, J
Abstract : The slowing of the conduction of an impulse travelling in the relative refractory period of a prior impulse was studied in single short toe extensor motor units in man. Paired electrical stimuli were delivered to the peroneal nerve and single motor unit recordings were achieved by special electromyographic techniques. The delay of the second impulse, propagated during the relative refractory period of the prior impulse, limited the unit discharge, frequency. The shortest motor unit response interval ranged from 3 to 5 ms and was inversely related to the axonal conduction velocity. The delay of the second impulse in the proximal nerve segment was most pronounced close to the stimulus point but continued during propagation for several milliseconds. Further delay occurred distally. The slowing of the conduction of the second impulse after delivering paired electrical nerve stimuli offers a new parameter in single motor unit studies and also makes it possible to measure the axonal refractory period after electrical nerve excitation without using blocking nerve impulses.